A nurse by any other name? An international comparison of nomenclature and regulation of healthcare assistants - Jennifer Jackson; Farida Gadimova; Sandra Epko (Elsevier, 2024)
Background: Across international healthcare systems, healthcare assistant roles have proliferated, in part to decrease nursing costs and support workplace staffing. There is a lack of consensus about the professional title for healthcare assistants, and whether this group requires professional regulation. The variety of terms for healthcare assistants has resulted in confusion around their scope of practice and role within the healthcare team, which may influence patient care. Aim: We aimed to identify the terminology used for healthcare assistants across English speaking countries and determine the international status of professional regulation of healthcare assistants. Method: We conducted a deductive, structured search for healthcare assistant roles that were codified on English-language nursing regulator websites in each jurisdiction in Australia, New Zealand, USA, Canada, Ireland, and the United Kingdom. We assessed what terminology were used for healthcare assistant roles in each area, and whether they were regulated by a professional regulator, such as a college of nursing. Results: Across 77 jurisdictions, we identified 37 different terms for healthcare assistants. The most frequent term was Certified Nurse Aid with 24 uses, and Certified Nursing Assistant with 13 uses. The majority of healthcare assistants are not professionally regulated. Only 12 jurisdictions have professional regulation programs for healthcare assistants, all in the USA. Conclusion: There is an urgent need for international consensus about the nomenclature for healthcare assistants, so the healthcare assistant workforce can be supported, and their work evaluated via research studies. Regulators can consider how to engage with healthcare assistants and protect the public, as healthcare assistants provide an increasing proportion of patient care.